Experimental Study of High-Performance Concrete Corbels with Hybrid Fiber Reinforced Concrete (HyFRC) - Nazir, Nazihah Shahirah (IRC, 2019)
Corbel are structural members or block projecting from a wall, commonly used in industrial building to support a ceiling, beam, or the roof overhang itself. However, the conventional concrete that used for its construction has neither inherent ductility nor durability. This report presented the result of an experimental study on the behavior of corbels made with Hybrid Fiber Reinforced Concrete (HyFRC). Several testings was conducted to understand the mechanical properties of HyFRC that is used as a mixture design for corbel. A total of 4 corbels were tested. The primary variables of the investigation were the presence of secondary reinforcement (stirrup) and shear span to depth ratio (a/d) of 1.0 and 0.75 was tested. All the corbels failed in a stable and ductile manner. The behavior of the corbels during testing and the analysis of the result indicate that the presence of secondary reinforcement and different a/d ratio affecting the shear strength of the corbels, i.e. the corbel with secondary reinforcement and a/d = 0.75 displayed higher deflection and ultimate shear load capacity compare to the corbel without and with secondary reinforcement of a/d = 1.0.